Degradation of nuclear oncoproteins by the ubiquitin system in vitro. - Ciechanover, A (1991)
Nuclear oncoproteins are among the most rapidly degraded intracellular proteins. Previous work has implicated the ubiquitin-mediated proteolytic system in the turnover of short-lived intracellular proteins. In the present study, we have evaluated the potential role of the ubiquitin system in the degradation of the specific nuclear oncoproteins encoded by the N-myc, c-myc, c-fos, p53 and E1A genes. Each of these nuclear oncoproteins was synthesized in vitro by transcription of the appropriate cDNA and translation of the resulting mRNA in the presence of [35S]methionine. Degradation of labeled proteins was monitored in the ubiquitin cell-free system. ATP stimulated the degradation of all the proteins between 3- and 10-fold. The degradation was completely inhibited by neutralizing antibody directed against the ubiquitin-activating enzyme, E1, the first enzyme in the ubiquitin-mediated proteolytic cascade. Moreover, degradation in E1-depleted lysates could be restored in each case by the addition of affinity-purified E1. These data suggest that the ubiquitin system mediates the degradation of these oncoproteins in vitro. Degradation of other proteins, such as superoxide dismutase, cytochrome c, enolase, RNase A, and ornithine decarboxylase, is not mediated by the ubiquitin cell-free system. This suggests that the nuclear oncoproteins studied here possess specific signals that target them for rapid turnover by this proteolytic pathway. Furthermore, the relative sensitivity to degradation of various E1A mutants in vivo is also maintained in the cell-free system, suggesting that the ubiquitin pathway may play a role in the cellular degradation of these proteins as well.